2018
DOI: 10.1016/s1473-3099(18)30069-0
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of lymphatic filariasis in west African urban areas: is implementation of mass drug administration necessary?

Abstract: Lymphatic filariasis in Africa is caused by the parasite Wuchereria bancrofti and remains a major cause of morbidity and disability in 74 countries globally. A key strategy of the Global Programme for the Elimination of Lymphatic Filariasis, which has a target elimination date of 2020, is the treatment of entire endemic communities through mass drug administration of albendazole in combination with either ivermectin or diethylcarbamazine. Although the strategy of mass drug administration in combination with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…Current estimates indicate that despite remarkable mass drug administration (MDA) programs, millions of people are currently infected with lymphatic filariasis, which is considered one of the leading global causes of disability (Gyapong et al, 2018). Furthermore, there are many areas of the world where MDA is not expected to eradicate this disease, so greater mosquito control efforts may be needed to accomplish this goal (Koudou et al, 2018). Moreover, C. quinquefasciatus has established itself as the dominant vector of avian malaria on many islands, and in some instances caused the extinction of many rare bird species (LaPointe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Current estimates indicate that despite remarkable mass drug administration (MDA) programs, millions of people are currently infected with lymphatic filariasis, which is considered one of the leading global causes of disability (Gyapong et al, 2018). Furthermore, there are many areas of the world where MDA is not expected to eradicate this disease, so greater mosquito control efforts may be needed to accomplish this goal (Koudou et al, 2018). Moreover, C. quinquefasciatus has established itself as the dominant vector of avian malaria on many islands, and in some instances caused the extinction of many rare bird species (LaPointe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the same line, Rao et al [38] recorded persistent W. Bancrofti infection in Sri Lanka that has low-level persistence of LF following multiple rounds of MDA in American Samoa. Recent empirical evidence has demonstrated that EPHP does not always lead to elimination of transmission (EOT) [2,39]. Residual infection remaining after MDA cessation can lead to resurgence and reintroduction [40,41], with longterm persistence dependent on a range of factors [35], including the presence of W. bancroftiinfected mosquitoes [2,39].…”
Section: Detection Of Wuchereria Bancrofti Dna In Anopheles Gambiae Smentioning
confidence: 99%
“…Recent empirical evidence has demonstrated that EPHP does not always lead to elimination of transmission (EOT) [2,39]. Residual infection remaining after MDA cessation can lead to resurgence and reintroduction [40,41], with longterm persistence dependent on a range of factors [35], including the presence of W. bancroftiinfected mosquitoes [2,39]. Importantly, we detected W. bancrofti mf in Odienné, even if at low prevalence (0.16%) and low microfilaremia (32.0 Mf/mL).…”
Section: Detection Of Wuchereria Bancrofti Dna In Anopheles Gambiae Smentioning
confidence: 99%
See 1 more Smart Citation
“…Current estimates indicate that despite remarkable mass drug administration (MDA) programs, millions of people are currently infected with lymphatic filariasis, which is considered to be one of the leading global causes of disability (Gyapong et al 2018). Furthermore, there are many areas of the world where MDA is not expected to eradicate this disease, but mosquito control could be the key to eliminating this disease (Koudou et al 2018). Moreover, Cx.…”
Section: Introductionmentioning
confidence: 99%